2016
DOI: 10.1002/2015jd024576
|View full text |Cite
|
Sign up to set email alerts
|

Interannual to interdecadal variability of winter and summer southern African rainfall, and their teleconnections

Abstract: Original citation: Dieppois, B. , Pohl, B. , Rouault, M. , New, M. , Lawler, D. and Keenlyside, N. (2016) Interannual to Interdecadal variability of winter and summer southern African rainfall, and their teleconnections. Abstract This study examines for the first time the changing characteristics of summer and winter southern African rainfall and their teleconnections with large-scale climate through the dominant time scales of variability. As determined by wavelet analysis, the austral summer and winter rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
94
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(107 citation statements)
references
References 126 publications
(280 reference statements)
10
94
0
Order By: Relevance
“…The small number of stations contributing to the CRU data estimate, combining both weak and strong drought signals because of the complex topography of the region is one reason for the uncertainty in the observational analysis. Further, the length of the station data is likely also important: the analysed region has a quasi 40 years component (Dieppois et al 2016) that underlies the previous severe droughts recorded in 1930s and 1970s, and the records' length is bound to reflect this multidecadal variability in rainfall.…”
Section: Synthesismentioning
confidence: 99%
“…The small number of stations contributing to the CRU data estimate, combining both weak and strong drought signals because of the complex topography of the region is one reason for the uncertainty in the observational analysis. Further, the length of the station data is likely also important: the analysed region has a quasi 40 years component (Dieppois et al 2016) that underlies the previous severe droughts recorded in 1930s and 1970s, and the records' length is bound to reflect this multidecadal variability in rainfall.…”
Section: Synthesismentioning
confidence: 99%
“…Positive (negative) ENSO events are correlated with high (low) pressure over Southern Africa that produce anomalous midtropospheric descent (ascent) and moisture divergence (convergence) that suppresses (enhances) convection, resulting in lower (higher) than average precipitation (Crétat et al, ; Hoell et al, ; Pohl et al, ; Ratnam et al, ). The correlation coefficient between precipitation and December–March (Austral summer) Pacific sea surface temperature anomalies are estimated to be −0.30 to ≥−0.4 (≥90% level (Dieppois et al, ; Hoell et al, ; Saji & Yamagata, ), but Hoell et al (, among others) also show that this is strongly modulated by the concurrent activity of the IOD. Depending on the phase of the subtropical IOD, it can either complement or disrupt the precipitation response to ENSO.…”
Section: Atmospheric Hazardsmentioning
confidence: 99%
“…When ENSO and the subtropical IOD were in phase, Southern Africa precipitation is only marginally reduced during El Niño, and precipitation is only marginally enhanced during La Niña. Other authors have suggested that the Pacific Decadal Oscillation may also have a role in modulating ENSO‐driven precipitation anomalies (e.g., Dieppois et al, ; S. Wang et al, ).…”
Section: Atmospheric Hazardsmentioning
confidence: 99%
“…Southern Africa is a region of pronounced climate variability on a range of scales (Tyson et al, 1975;Mason, 1990Mason, , 1995Lindesay, 1988;Reason, 1998;Reason et al, 2000;Richard et al, 2001;Reason and Rouault, 2002;Rouault et al, 2002;Colberg et al, 2004;Cook et al, 2004;Washington and Preston, 2006;Singleton and Reason, 2007;Pohl et al, 2009Pohl et al, , 2010Crétat et al, 2012;Malherbe et al, 2014;Grimm and Reason, 2015;Dieppois et al, 2016) whose relationships with regional circulation systems are still not well understood. One such prominent circulation system in the mid-levels of the troposphere over southern Africa that occurs during austral spring, summer and early autumn is the Botswana High.…”
Section: Introductionmentioning
confidence: 99%